2010
DOI: 10.1111/j.1365-2133.2010.10063.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reflectance confocal microscopy of shave biopsy wounds: feasibility of intraoperative mapping of cancer margins

Abstract: Background Reflectance confocal microscopy (RCM) images skin at cellular resolution and has shown utility for the diagnosis of nonmelanoma skin cancer in-vivo. Topical application of Aluminum Chloride (AlCl3) enhances contrast in RCM images by brightening nuclei. Objective To investigate feasibility of RCM imaging of shave biopsy wounds using AlCl3 as a contrast agent. Methods AlCl3 staining was optimized, in terms of concentration versus immersion time, on excised tissue ex-vivo. RCM imaging protocol was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 35 publications
(63 reference statements)
3
51
0
1
Order By: Relevance
“…The article by Meschieri et al [9] reviews the value of in-vivo reflectance confocal microscopy as a tool in cutaneous oncology. One of his co-authors, Millind Rajadhyaksha has been crucial in developing this technology and bringing it to practical application [10][11][12][13][14]. As the major technical limitation of this method is the image depth of up to 300 μm, its main role may be in early detection of skin malignancies, specifically in directing necessary biopsies and avoiding unnecessary ones.…”
Section: Fortschritte In Der Dermatologiementioning
confidence: 99%
“…The article by Meschieri et al [9] reviews the value of in-vivo reflectance confocal microscopy as a tool in cutaneous oncology. One of his co-authors, Millind Rajadhyaksha has been crucial in developing this technology and bringing it to practical application [10][11][12][13][14]. As the major technical limitation of this method is the image depth of up to 300 μm, its main role may be in early detection of skin malignancies, specifically in directing necessary biopsies and avoiding unnecessary ones.…”
Section: Fortschritte In Der Dermatologiementioning
confidence: 99%
“…For the noninvasive skin cancer diagnostics the application of biomedical imaging is known, such as PET [4], optical coherence tomography [5,6], confocal microscopy [7]. However, the imaging methods are labour-consuming and expensive, and their application is reasonable for updating the already established diagnosis, planning and control of the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Reflectance confocal microscopy (RCM) is probably the most accepted non-invasive technique to be used in skin cancer detection, at the moment, and it is widely used in clinical trials for this purpose [31][32][33][34][35]. In RCM, out of focus light is eliminated by situating a spatial pinhole at the focal point of the beam.…”
Section: Reflectance Confocal Microscopymentioning
confidence: 99%
“…Moreover, a two-step algorithm was developed to diagnose skin tumors [35]. Scope et al used aluminium chloride to increase the contract of the images and by varying the depth of optical sectioning, three consistent patterns of tumorous margins were identified as: epidermal margins, peripheral dermal margins, and deep dermal margins [33]. In that research, basal cell carcinomas were identified at peripheral or deep dermal margins and honeycomb patterns of squamous cell carcinomas were also identified at the epidermal margins [33].…”
Section: Reflectance Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation